Magmas inhibition as a potential treatment strategy in malignant glioma - Di, Kaijun (J Neurooncol, 2018)
PURPOSE: Magmas (mitochondria-associated protein involved in granulocyte-macrophage colony-stimulating factor signal transduction) is a nuclear gene that encodes the mitochondrial import inner membrane translocase subunit Tim16. Magmas is highly conserved, ubiquitously expressed in mammalian cells, and is essential for cell viability. Magmas expression levels are increased in prostate cancers and pituitary adenomas. Moreover, silencing Magmas by RNAi sensitizes pituitary adenoma cells to pro-apoptotic stimuli and induces a G0/G1 accumulation. The aim of this study was to examine whether inhibition of Magmas by small molecule inhibitors could be beneficial for the treatment of malignant gliomas. METHODS: We evaluated the expression of Magmas in patient-derived glioblastoma tissue samples and xenograft models. We studied the feasibility of a small molecule Magmas inhibitor (BT#9) as a therapeutic agent in stable human glioma cell lines and high-grade patient derived glioma stem-like cells. RESULTS: Magmas was overexpressed in tissue sections from glioma patients and xenografts. In vivo studies revealed that BT#9 could cross the blood-brain barrier in the animal model. Magmas inhibition by BT#9 in glioma cell lines significantly decreased cell proliferation, induced apoptosis along with vacuole formation, and blocked migration and invasion. In addition, BT#9 treatment decreased the respiratory function of glioma cells, supporting the role that Magmas serves as a ROS (reactive oxygen species) regulator. CONCLUSIONS: This is the first study on the role of Magmas in glioma. Our findings suggest that Magmas plays a key role in glioma cell survival and targeting Magmas by small molecule inhibitors may be a therapeutic strategy in gliomas.